Experimental Study on the Effect of Dust Deposition on a Car Park Photovoltaic System with Different Cleaning Cycles - Khaled M. Alawasa (Sustainability, 2021)
For a decade, investments in solar photovoltaic (PV) systems have been increasing exponentially in the Middle East. Broadly speaking, these investments have been facing tremendous challenges due to the harsh weather in this particular part of the world. Dust accumulation is one the challenges that negatively affects the performance of solar PV systems. The overall goal of this paper is to thoroughly investigate the effect of dust accumulation on the energy yield of car park PV systems. With this aim in mind, the paper presents scientific values for further research and opens the horizon for attracting further investments in solar PV systems. This study is based on a real PV system in the Sultanate of Oman and considers different cleaning cycles for 16 months (from 29 July 2018 to 10 November 2019). Furthermore, four different PV groups were assessed, and the system was monitored under different cleaning frequencies. In general, it was found that dust accumulation has a significant impact; under 29-day, 32-day, 72-day, and 98-day cleaning cycles, the average percentages of energy loss due to soiling were 9.5%, 18.2%, 31.13%, and 45.6%, respectively. In addition, the dust effect has a seasonal variation. The study revealed that dust accumulation has a more negative impact during summer than during winter. During summer, the energy losses due to soiling were 8.7% higher than those during winter. The difference was attributed to different environmental conditions, with high humidity and low wind speed being the main factors that worsen the impact of dust during summer. Based on the findings of this research, a monthly cleaning program is highly recommended in the city of Muscat.